1970
DOI: 10.1104/pp.45.4.435
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Protein Synthesis by Plastids of Phaseolus vulgaris

Abstract: Etioplasts are converted to chloroplasts when etiolated leaves of higher plants are placed in the light. Chlorophyll is formed during this conversion, the ability to photosynthesize develops (2,8,19,26,31), and the plastids increase in size and form their characteristic lamellar structures (9,24). Development of the ability to photosynthesize depends both on the formation of chlorophyll and on the formation of protein (11,20,21 tine were used throughout. They were grown in darkness for 6 to 8 days, or they wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…It is also possible that protein synthesis is very low in organelles from dark-grown plants, so that translation of all etioplast mRNAs, including LS mRNA, is markedly reduced. However, other studies (26,32) have shown that in the first 48 hr of greening, there appears to be an increase of only 3-fold in the proteinsynthesizing capacity of isolated plastids. A change of this magnitude may reflect the increase in total plastid RNA resulting from gene amplification and not be related to increased translational efficiency.…”
Section: Discussionmentioning
confidence: 89%
“…It is also possible that protein synthesis is very low in organelles from dark-grown plants, so that translation of all etioplast mRNAs, including LS mRNA, is markedly reduced. However, other studies (26,32) have shown that in the first 48 hr of greening, there appears to be an increase of only 3-fold in the proteinsynthesizing capacity of isolated plastids. A change of this magnitude may reflect the increase in total plastid RNA resulting from gene amplification and not be related to increased translational efficiency.…”
Section: Discussionmentioning
confidence: 89%
“…For some investigators working on etiolated Euglena [5] as well as on higher plants [6,7], the etiolated material exposed to light leads necessarily to a de novo synthesis of new proteins. For others, etiolated plastids contain all or at least a large part of the proteins necessary for the building of lamellae and grana [8] and consequently, it has been proposed that structural changes might be due to a reorganization of the existing protein molecules rather than to a de novo protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies made of protein synthesis in chloroplasts isolated from higher plants, most notably from bean (9,23), pea (29), spinach (35), tobacco (4,5,11,14), tomato (20), and wheat (2). Little is known, however, about the development of the capacity for protein synthesis during chloroplast biogenesis, and with one exception (9) studies comparable to those cited above have not been carried out using isolated etioplasts or immature chloroplasts.…”
mentioning
confidence: 99%
“…Little is known, however, about the development of the capacity for protein synthesis during chloroplast biogenesis, and with one exception (9) studies comparable to those cited above have not been carried out using isolated etioplasts or immature chloroplasts. Indeed, the development of an extraction medium for isolating structurally intact etioplasts (from maize) has only recently been reported (21).…”
mentioning
confidence: 99%